2016
DOI: 10.1136/bmjopen-2016-013897
|View full text |Cite
|
Sign up to set email alerts
|

‘You can't be a person and a doctor’: the work–life balance of doctors in training—a qualitative study

Abstract: ObjectivesInvestigate the work–life balance of doctors in training in the UK from the perspectives of trainers and trainees.DesignQualitative semistructured focus groups and interviews with trainees and trainers.SettingPostgraduate medical training in London, Yorkshire and Humber, Kent, Surrey and Sussex, and Wales during the junior doctor contract dispute at the end of 2015. Part of a larger General Medical Council study about the fairness of postgraduate medical training.Participants96 trainees and 41 traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 42 publications
4
113
0
5
Order By: Relevance
“…If this is the case, it will have significant implications for medical workforce planning, retention and recruitment. As more early‐career doctors in many countries are women, 26,35,36 and if more male early‐career doctors now wish to achieve a better work‐life balance in their training posts and jobs, specialties, which have been traditionally male‐dominated and perceived to have long hours and inflexible working patterns, may struggle to recruit 28,36‐40 . Career breaks may become more common for both genders as these appear to be increasingly related to a wish to improve work‐life balance 19,38,41,42 …”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, it will have significant implications for medical workforce planning, retention and recruitment. As more early‐career doctors in many countries are women, 26,35,36 and if more male early‐career doctors now wish to achieve a better work‐life balance in their training posts and jobs, specialties, which have been traditionally male‐dominated and perceived to have long hours and inflexible working patterns, may struggle to recruit 28,36‐40 . Career breaks may become more common for both genders as these appear to be increasingly related to a wish to improve work‐life balance 19,38,41,42 …”
Section: Introductionmentioning
confidence: 99%
“…It appears to be contributing to resident and trainee dissatisfaction and an increasing pattern of residents and trainees wishing to take time out of training, quit training or move into medical jobs without patient contact. [13][14][15][16][17][18] Responses to the challenge of tension between education and service have been diverse. These have included calls for the transformation of medical education, such as shifting from traditional ward teams to more education-oriented services, 19,20 and alternative pedagogic methods, such as simulation-based education.…”
Section: Resultsmentioning
confidence: 99%
“…Women are typically saddled with the work of keeping the home and when this is added to that of the office including the long hours spent in the hospital can be quite challenging. The work load is worse among those with children (Rich et al, 2016). A study among 96 trainees and 41 trainers involved in the United Kingdom postgraduate medical training reported that female trainee doctors suffered more from work-life imbalance and tended to chose specialties that appeared more favourable to achieving a work-life balance (Rich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The work load is worse among those with children (Rich et al, 2016). A study among 96 trainees and 41 trainers involved in the United Kingdom postgraduate medical training reported that female trainee doctors suffered more from work-life imbalance and tended to chose specialties that appeared more favourable to achieving a work-life balance (Rich et al, 2016). Also, female doctors are more likely to develop burnout syndrome compared with their male counterparts (Amoafo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%